Everyday Identity Change. Convergences and Challenges, Achievements and Agendas of Recent Research - Todd, Jennifer (PARTECIPAZIONE E CONFLITTO, 2019)
This article reviews some recent trends in research on everyday identity change. It argues that this field of research makes an important contribution to the explanation of political change and social transformation. It is particularly relevant to research on participation, social movements and contentious politics: like the latter, it emphasizes relationality, temporality and context, not simply variables and generalization; like the latter, it focusses on agency, choice and social practice as well as structure, power and constraint. Its focus on moving out from exclusivist, closed and oppositional forms of group identity is of particular interest. The article outlines some of the challenges and achievements of this field of research and highlights four areas where significant work exists and where it may usefully be developed further. In particular it focusses on: boundary work, and the informal nudging of boundaries towards greater permeability; identity-work, and the challenge of comparison; (once)-dominated and (once-)dominant groups, and their distinctive forms of identity change; and the interrelation of everyday, institutional and political processes. It argues for the need to incorporate analysis of everyday change in multi-levelled explanations of socio-political outcomes.